1985
DOI: 10.1148/radiology.156.3.4023222
|View full text |Cite
|
Sign up to set email alerts
|

Central nervous system anoxic-ischemic insult in children due to near-drowning.

Abstract: An analysis of admission and follow-up CT examinations of the brains of 17 children who had nearly drowned (15 of whom were comatose and two of whom were conscious on admission) indicated that a normal initial CT scan is common in the majority of comatose patients, a severe neurologic outcome may develop in spite of a normal initial CT examination, and abnormal initial or follow-up CT findings indicate the strong but not inevitable probability of a severe neurologic outcome. We conclude that when there is no h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…An initially normal CT in a comatose patient should not be re-assuring [138, 139]. Comatose pediatric drowning victims who have an initial abnormal head CT or a normal CT with a subsequent abnormal CT have poor outcome [139].…”
Section: Neuromonitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…An initially normal CT in a comatose patient should not be re-assuring [138, 139]. Comatose pediatric drowning victims who have an initial abnormal head CT or a normal CT with a subsequent abnormal CT have poor outcome [139].…”
Section: Neuromonitoringmentioning
confidence: 99%
“…Comatose pediatric drowning victims who have an initial abnormal head CT or a normal CT with a subsequent abnormal CT have poor outcome [139]. Retrospective studies concluded that if there was no clinical evidence of trauma, CT is not necessary [138, 139]. Despite this, intracranial hemorrhage may be present following CA [140].…”
Section: Neuromonitoringmentioning
confidence: 99%
“…Taylor et al found that 12 of 17 children (71%) had normal CTs following a drowning event (7). Abnormal findings consisted of either diffuse edema and/or bilateral basal ganglia infarction.…”
Section: Discussionmentioning
confidence: 99%
“…No large studies exist that describe the cranial computed tomography (CT) findings in children with drowning; only a few, small retrospective reviews examine this subject (6,7). The primary purpose of this study is to better define both the patterns and incidence of cranial CT abnormalities found in children following submersion injury.…”
mentioning
confidence: 99%
“…Early prognostic of good outcome versus significant neurological deficit or death is important for correctly stratifying patient management 1,2 . Magnetic resonance image (MRI) and computed tomographic findings of acute hypoxia ischemic injury are often subtle [1][2][3] . we describe the findings of early proton magnetic resonance spectroscopy ( 1 H MRS) that helped to predict the prognosis.…”
mentioning
confidence: 99%